The textual effects of David Walker's Appeal : print-based activism against slavery, racism, and discrimination, 1829-1851 - Dinius, Marcy J. (Material texts., 2022)
"Historians and literary historians alike recognize David Walker's Appeal to the Coloured Citizens of the World (1829-30) as one of the most politically radical and consequential antislavery texts ever published, yet the pamphlet's significant impact on North American nineteenth century print-based activism has gone underexamined. In The Textual Effects of David Walker's Appeal Marcy J. Dinius offers the first in-depth analysis of Walker's argumentatively and typographically radical pamphlet and its direct influence on five Black and Indigenous activist authors, Maria W. Stewart, William Apess, William Paul Quinn, Henry Highland Garnet, and Paola Brown, and the pamphlets that they wrote and published in the United States and Canada between 1831 and 1851"--